2005
DOI: 10.1074/jbc.m410081200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α Stimulation of Rac1 Activity

Abstract: We have previously demonstrated that both isoprenylcysteine carboxylmethyltransferase (ICMT) and one of its substrates, the RhoGTPase Rac1, are critical for the tumor necrosis factor ␣ (TNF␣) stimulation of vascular cell adhesion molecule-1 expression in endothelial cells (EC). Here, we have shown that ICMT regulates TNF␣ stimulation of Rac1 activity. TNF␣ stimulation of EC increased the membrane association of Rac1, an event that is essential for Rac1 activity. ICMT inhibitor Nacetyl-S-farnesyl-L-cysteine (AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…5). This assessment is also consistent with a previous report showing an increase in Rac binding to Rho GDI in Icmt-deficient MEFs (34). Interestingly, there is evidence that phosphorylation of Ser-188 of RhoA increases its binding to RhoGDI (36).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…5). This assessment is also consistent with a previous report showing an increase in Rac binding to Rho GDI in Icmt-deficient MEFs (34). Interestingly, there is evidence that phosphorylation of Ser-188 of RhoA increases its binding to RhoGDI (36).…”
Section: Discussionsupporting
confidence: 81%
“…4). Previous studies have also seen a link between Icmt activity and RhoGTPase function (34,35), and some of these effects have been ascribed to a reduced stability of Rho proteins when their methylation is impaired (23). In genetically null cells, derived from Icmt knock-out mice, lower levels of Rho protein are observed (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional post-prenylation modifications of Rac1, such as carboxyl methylation and proteolysis, are not required for complex formation with RhoGDI (77). On the contrary, lack of carboxyl methylation enhanced binding of Rac1 to RhoGDI in endothelial cells (78). Thus, to be able to conduct quantitative biochemical studies on Rac-RhoGDI interactions, we created stable Rac1(GDP)⅐RhoGDI and Rac2(GDP)⅐RhoGDI complexes in vitro by mixing recombinant Rac(1 or 2)(GDP), expressed in E. coli and prenylated in vitro, with a 2-or 4-fold excess of recombinant RhoGDI, also expressed in E. coli.…”
Section: Generation Of Rac1(gdp)⅐rhogdi and Rac2(gdp)⅐rhogdi Complexementioning
confidence: 97%
“…A recent study found that the membrane association and biological function of farnesylated Ras proteins, but not of geranylgeranylated Rho GTPases, were impaired in the absence of Rce1 or Icmt expression (22). However, other studies using pharmacologic inhibitors suggested that geranylgeranylated protein function also depends on these modifications (51,52). Therefore, to elucidate whether the specific isoprenoid modification of a Rho GTPase dictates a dependence on Rce1-catalyzed -AAX cleavage and Icmt-mediated carboxyl methylation, we evaluated the subcellular localization of Rho GTPases in MEF cell lines deficient in Rce1 (Rce1 Ϫ/Ϫ ) or Icmt (Icmt Ϫ/Ϫ ).…”
Section: The Membrane Association And/or Function Of Rho Gtpases Is Dmentioning
confidence: 99%